Exploring the Adoption and Evaluation of E-Commerce in SMEs: Planning and Implementation Stages - Lin, Chad; Huang, Y. (Academy of Taiwan Information Systems Research, 2006)
ABSTRACT E-commerce has been touted as the must have item for participation in the knowledge economy for all organizations. However, SMEs have generally been slow to adopt and evaluate e-commerce. This paper describes research findings from a study conducted to examine and explore the e-commerce adoption and evaluation issues and practices of Australian SMEs during the planning and implementation stages. The results showed that most SMEs failed to link their objectives for e-commerce adoption with their organizational goals as well as to involve users during the planning stage. In addition, pre-project justification process and change management were often not properly carried out. Although it was found that almost all senior executives and managers were committed to the IT investments in e-commerce during the implementation stage, most of these organizations did not manage user resistance effectively. Moreover, it was also disappointing to see that most SMEs failed to conduct IT investment evaluation processes during the implementation stage. Finally, no formal IT benefits realization methodology was carried out in any of the SMEs interviewed.